Climate change manifestations and impacts in The Sokoto Close-Settled Zone, Northwestern Nigeria - Abubakar Magaji Jibrillah,; Lam, Kuok Choy; Mokhtar Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Located within the Semi-Arid zone of Northwestern Nigeria, Sokoto Close-Settled Zone (SCSZ), has over the years been suffering from climate change and its associated socio-economic consequences. These negatively affects both the natural ecosystem and the livelihood of the inhabitant of the area. Using multi-temporal Landsat data and meteorological data such as rainfall and temperature records, as well as geospatial analyses such as Normalised Difference Vegetation Index (NDVI), image differencing and simple statistical techniques, this research identified and assess differentmanifestations of climate change in the area. Implications of these on the livelihoods of the people in the area were also discussed. The result indicated an increasing trend in both minimum and maximum temperatures as well as a progressive decline in the rainfall pattern of the area over the last 10 years. Also, the area recorded over 40% loss of vegetation cover within the same period. The cumulative effects of the above scenarios, leads to decline in crop and livestock productivity, destruction of farmlands and grazing areas and increasing water scarcity, among others, all of which negatively affect the livelihood of the inhabitant of the area, leading to declining family income, food shortages, and in some extreme cases malnutrition and diseases. Mitigation and adaptation strategies including sustainable land and water management practices, ecosystem-based adaptations, afforestation, agroforestry, alternative sources of livelihood as well as civic and environmental education were also suggested.